2007
DOI: 10.1007/s11606-007-0298-x
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-sectional Measurement of Medical Student Empathy

Abstract: BACKGROUND: Empathy is important in the physicianpatient relationship. Prior studies have suggested that physician empathy may decline with clinical training.OBJECTIVE: To measure and examine student empathy across medical school years. DESIGN AND PARTICIPANTS:A cross-sectional stud of students at Boston University School of Medicine in 2006. Incoming students plus each class near the end of the academic year were surveyed. MEASUREMENTS:The Jefferson Scale of Physician Empathy-Student Version (JSPE-S), a valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

55
402
23
42

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 447 publications
(522 citation statements)
references
References 42 publications
55
402
23
42
Order By: Relevance
“…There is a need to further explore why most Asian students have almost similar scores but lower than the American studies. 8,20,21 The empathy scores at the entry point of medical school is much less than those found in US by Chen et al (115.5), Hojat et al (114.5) but similar to that from Iran (110.3). 8,11,14 The curriculum in this college is different in many respects from medical schools in US, Japan and Iran.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…There is a need to further explore why most Asian students have almost similar scores but lower than the American studies. 8,20,21 The empathy scores at the entry point of medical school is much less than those found in US by Chen et al (115.5), Hojat et al (114.5) but similar to that from Iran (110.3). 8,11,14 The curriculum in this college is different in many respects from medical schools in US, Japan and Iran.…”
Section: Discussionmentioning
confidence: 67%
“…8 There were no non-responders as all those present on the day of assessment completed the questionnaire (Table 1). This is in contrast to the poor response rate of third year students (77.2%) in the study by Chen et al 8 in which incidentally a decrease in empathy scores was also found whereas in this study significant decline was evident only in seventh semester. From this study we confirmed our first hypothesis that empathy declines during medical education but it reaches significant level only in seventh semester.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations